Harmony in Contrast: Architectural Innovation in Preserving Candi Kimpulan in Yogyakarta, Indonesia - Mutaqi, Ahmad Saifudin; Suparwoko; Setiawan, Agus; Salura, Purnama; Lake, Reginaldo Christopori (MAJ - Malaysia Architectural Journal, 2025)
The shift in cultural preservation paradigms has necessitated a holistic approach to safeguarding cultural heritage in an increasingly globalized world prone to pressure and homogenization. Documents such as the Nara Document (1994), the Ciloto Agreement (2003), and the protocols established during meetings in Bangkok, notably the Hoi-An Protocol (2009), underscore the importance of appreciating cultural diversity, preserving intangible aspects, and fostering stakeholder cooperation in heritage conservation within their respective environments. The discovery of the 9th-century Candi Kimpulan archaeological site during the library’s construction at Universitas Islam Indonesia (UII) sparked questions about reconciling modern architectural design with efforts to preserve cultural heritage. This research aims to unveil the architectural design process of the UII library, which strikes a compromise between modernity and the preservation of Candi Kimpulan. The intrinsic case study research method is employed to focus on the architectural elements of the library designed as cultural preservation strategies. Placing the library building in the development zone with surrounding structures in the buffer zone serves both as circulation and protection for the core zone of Candi Kimpulan. This design exemplifies harmony in the contrast between modernity and cultural preservation. The study demonstrates that modern architectural design can be reconciled with efforts to preserve cultural heritage through appropriate strategies, such as zoning division and circulation design.